SERVICE BASED PLATFORM WORKERS: RESHAPING CAREERS-A STUDY WITH REFERENCE TO MANGALURU CITY - Quadras, Avitha Maria (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India off-late has been witnessing a fundamental reorientation in its work culture. Fourth Industrial revolution and the presence of a multi- generational workforce with varied requirements have been a catalyst to the same. On one hand, concept of virtual reality, flexi-time, flexi-workspace and flexi staffing became a reality for few, while on the other many industries were not doing well. A transition was observed. Numerous contract or part-time jobs in the delivery, home services, food and beverage, and e-commerce sectors have evolved. These positions are ideal for freelancers and individuals seeking short-term projects. These employees called gig workers have become a part of developing India and are contributing in an immense manner to the gig economy. Interestingly both the unskilled and skilled workers together sought relief in the gig economy.